Production of cytokines by cell-effectors of natural cytotoxicity system in mice under development of Lewis lung carcinoma - Ye. Yu. Sherstoboyev; O. A. Kaplya; Ye. P. Zuyeva; T. G. Razina; O. I. Epstein (Бюллетень сибирской медицины)
Cytokine production by cell-effectors of natural cytotoxicity system under Lewis lung carcinoma development in F1(CBAxC57B1/6) line mice has been studied. It has been revealed the increase of interleukin-1β (IL-1β) production and tumor necrosis factor-α (TNF-α) by peritoneal macrophages. At this the balance of cytokines produced by T-helpers (Th)  has  been displaced to Th2 side, IL-4 production has increased and interferon-γ (IFN-γ) and IL-2 production has decreased. The rise of IL-10 production by lymphocytes has been observed in the later terms of tumor development.